EFEITO DO SILDENAFIL SOBRE ALTERAÇÕES VASCULARES E DANO TECIDUAL INDUZIDOS PELO CHOQUE SÉPTICO - Silvério, Vanessa Kovalski (2015)
Septic shock, which is triggered by microbial products, is mainly characterized by an inadequate tissue perfusion caused by a decreased in blood pressure, vascular damage, hyporeactivity to vasoconstrictors and disseminated intravascular coagulation, which can lead to multiple organ dysfunction and death. Nitric oxide (NO) is an important player in the pathogenesis of sepsis and septic shock, having both protective and deleterious effects. Trials of nonselective NOS inhibitors have shown increased mean arterial pressure, but also increased pulmonary artery pressure and reduced cardiac output. Thus, despite the intense research, there was no clinical progress so far. Perhaps this is due to lack of compression of NO signaling pathways. There is a knowledge gap on the role of the NO-guanylate cyclase- guanosine 3 ', 5'-cyclic monophosphate (cGMP) pathway during the early stages of sepsis. Most work has studied the role of cGMP by inhibiting the enzyme responsible for its production (guanylate cyclase), however, in this work we chose to try the increased cGMP levels by inhibiting an enzyme responsible for their degradation, phosphodiesterase 5 (PDE5). In the early stages of shock occurs an intense release of vasoconstrictors agents, which can lead to ischemia damage. In this scenario, cGMP could play a key role counterbalancing these agents and preventing tissue damage. Sildenafil, a type-5 cGMP phosphodiesterase inhibitor, increase GMP at smooth muscle cells and promotes vasodilation .Thus, the purpose of this study was to investigate the effect of treatment with sildenafil in the early stages of sepsis. Male Wistar rats were divided into 2 groups of 16 animals each and submitted to either Cecal Ligation and Puncture (CLP) or the sham procedure. Eight hours after the procedure, the CLP and sham groups were randomly assigned to receive sildenafil (10 mg/kg orally) or vehicle. Twenty-four hours after the CLP or sham procedure, the mean arterial blood pressure, systolic and diastolic blood pressure and vascular reactivity to phenylephrine were evaluated. Additionally, blood samples were collected for measurement of nitric oxide (nitrate and nitrite), urea, creatinine, AST, ALT, lactate and CK.; hematological analyzes were also performed. Statistical significance was analyzed by two-way ANOVA followed by post hoc Bonferroni. The results shows that the CLP was able to reproduce the main characteristics of humans sepsis like as, systemic inflamation, hypotension, reduced response to vasoconstrictors, hypoxia and tissue damage. Interestingly, treatment with sildenafil improved and the organ hypoperfusion at early stages of sepsis reducing organ injury. Thus, phosphodiesterase inhibition may be a useful therapeutic strategy if administered at the proper window of opportunity.